ENTREPRENEURIAL LEADERSHIP AS A STRATEGY FOR IMPROVING MSME EMPLOYEE PERFORMANCE IN TEBING TINGGI CITY - Rizki Wulanita Batubara; Suci Etri Jayanti; Rapat Piter (CV. Radja Publika, 2026)
This study examines entrepreneurial leadership as a strategy for improving employee performance in micro, small, and medium enterprises (MSMEs) in Tebing Tinggi City. The research was designed as a quantitative explanatory survey involving 150 employees from culinary, trade, service, and creative-industry MSMEs. Entrepreneurial leadership was measured through opportunity recognition, vision articulation, risk management, creativity encouragement, and employee empowerment, while employee performance was assessed through work quality, quantity, timeliness, adaptability, and responsibility. Data were analyzed using descriptive statistics, validity and reliability tests, and simple linear regression. The illustrative findings indicate that entrepreneurial leadership has a positive and significant effect on employee performance (β = 0.624; t = 9.708; p < 0.001), explaining 39.0% of performance variance. Leaders who communicate growth opportunities, encourage initiative, tolerate calculated experimentation, and provide rapid feedback tend to create more adaptive and productive employees. The study contributes by shifting the focus from MSME owners’ business performance to employee-level outcomes in a secondary Indonesian city. Practically, MSME owners should institutionalize brief performance dialogues, idea-generation routines, delegated decision making, and learning-oriented evaluation to strengthen employee performance and business resilience.